Dialogue with the World: The Concept of Body according to Merleau-Ponty and Ramanuja - Alackapally, Sebastian (Journal of Dharma, 2010)
Wilson Edattukaran, Dialogue with the World: The Concept of Body according to Merleau-Ponty and Ramanuja. Delhi: Sri Satguru Publications, 2010, ISBN: 81-7030-928-X, pages xvi + 360.